2001
DOI: 10.1248/bpb.24.902
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Specific [3H]Nociceptin Binding in Rat Brain and Spinal Cord.

Abstract: Nociceptin (orphanin FQ), a heptadecapeptide isolated from rat and porcine brain, has been identified as the endogenous ligand of opioid receptor-like ORL1 receptor, an orphan G protein-coupled receptor. 1,2) The sequences of human, mouse and rat complementary DNA for the ORL1 receptor indicate a significant degree of homology with the 'classical opioid' receptors (m, d and k). [3][4][5][6][7] In spite of this homology with opioid receptors, potent opioid ligands fail to bind to ORL1 receptors. Nociceptin itse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Nor-BNI showed negligible affinity, consistent with prior reports [29], [30], as did GNTI. Surprisingly, despite its high affinity and lack of efficacy, JDTic only weakly inhibited the response to N/OFQ in a functional assay (inhibition of cyclic AMP production: pA 2  = 7.1, 95% CI = 5.9 to 8.3, Figure 4A).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Nor-BNI showed negligible affinity, consistent with prior reports [29], [30], as did GNTI. Surprisingly, despite its high affinity and lack of efficacy, JDTic only weakly inhibited the response to N/OFQ in a functional assay (inhibition of cyclic AMP production: pA 2  = 7.1, 95% CI = 5.9 to 8.3, Figure 4A).…”
Section: Resultssupporting
confidence: 91%
“…No binding was detected at 10 µM to the glucocorticoid receptor NR3C1 [28]. Nor-BNI's affinity for the opioid-like nociceptin/orphanin FQ receptor (NOP) is also negligible; one study found low affinity ( K i  = 780 nM) [29], while another detected no binding at 10 µM [30].…”
Section: Introductionmentioning
confidence: 99%
“…Determination of the binding affinity of nociceptin at the NOP receptor has been notoriously difficult and reported K i values vary widely (0.03-2 nM) due to differences in binding assays and unusual binding properties of nociceptin (see Dooley & Houghten, 2000). Furthermore, differences may exist in the binding affinity of nociceptin in the spinal cord and brain (Kusaka, Yamada & Kimura, 2001). Here, full efficacy was observed after spinal application of 10-μg (~5.…”
Section: Discussionmentioning
confidence: 96%